Fungsi Densitas Peluang Temporal (T-PDF) dari Dinamika Euro terhadap Dolar Amerika Serikat - Triyana Muliawati; . Kartono; Edi Cahyono (Journal of Science and Applicative Technology, 2019)
In this paper we discuss the dynamics of exchange rate of Euro (EUR) relative to United States dollar (USD). The data is observed from daily data in the period 1 January 2005 to 31 December 2012. In this period of global financial crisis which is affected the global economy. Therefore, an understanding of the exchange rate of EUR relative to USD is required. The Data is presented in the form of a diagram of a candlestick (candle). Statistical analysis on a mean of exchange rate of EUR relative to USD is applied to each monthly candle representation. The mean may vary per candle, which means that the mean as a function of time. A function of mean relative to time so commonly referred to as a moving average, or a trend. The continous of a trend is approached with linear interpolation and polynomial interpolation is based on the mean of the candle every month. The mean and standard deviation of exchange rate of EUR relative to USD generates a probability density function (pdf). A pdf is based on the assumption that the dynamics is normally distributed. The mean is dependent on time is called temporal probability density function (t-pdf). The trend of the dynamics of exchange rate of EUR relative to USD is implicitly represented in the t-pdf. By knowing t-pdf will help investors know the dynamics of the exchange rate of the EUR against the USD. Keywords: dynamics, exchange rate, candlestick, t-pdf